2022
DOI: 10.1177/19367244221078278
|View full text |Cite
|
Sign up to set email alerts
|

References to Evidence-based Program Registry (EBPR) Websites for Behavioral Health in U.S. State Government Statutes and Regulations

Abstract: U.S. state governments have the responsibility to regulate and license behavioral health care interventions, such as for addiction and mental illness, with increasing emphasis on implementing evidence-based programs (EBPs). A serious obstacle to this is lack of clarity or agreement about what constitutes “evidence-based.” The study’s purpose was to determine the extent to which and in what contexts web-based Evidence-based Program Registries (EBPRs) are referenced in state government statutes and regulations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…This is consistent with the findings of previous studies, which found either a general lack or restricted range of references to EBPRs on both state agency websites and within state-level behavioral health policies for the use of EBIs. 23 , 24 EBPRs are potentially valuable resources for identifying EBIs for behavioral health and for obtaining guidance for program implementation. Thus, increasing references to EBPRs in FOAs for federal funding of behavioral healthcare interventions would likely improve the FOA process and increase the societal impact of such interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the findings of previous studies, which found either a general lack or restricted range of references to EBPRs on both state agency websites and within state-level behavioral health policies for the use of EBIs. 23 , 24 EBPRs are potentially valuable resources for identifying EBIs for behavioral health and for obtaining guidance for program implementation. Thus, increasing references to EBPRs in FOAs for federal funding of behavioral healthcare interventions would likely improve the FOA process and increase the societal impact of such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that inclusion of EBPRs in legislative mandates for the use of evidence-based interventions could clarify and strengthen those mandates. 24 The same seems likely for purchasing levers as well.…”
Section: Introduction/backgroundmentioning
confidence: 95%
See 2 more Smart Citations
“…The variety of terms that have been associated with the concept of "evidence-based" include "research-based," "science-based," "best practice(s)," "empirically supported treatment," or "promising program or practice." Lee et al (2022) examines references to evidence-based behavioral health program registries in statutes and regulations of state agencies, and Magura et al (2022) examines state behavioral agency personnel's familiarity with behavioral health program registries. However, there is no study to date that examines the official definitions of terms related to the concept of "evidencebased" propagated by statutes and regulations that apply to state behavioral health agencies.…”
Section: Literature Reviewmentioning
confidence: 99%